MENTAL HEALTH AND FACTORS RELATED TO MENTAL HEALTH AMONG PAKISTANI UNIVERSITY STUDENTS - Sultan Akbar Shah; Hasan Zulfiqar; Mamoona Bibi; Abdul Raheem; Rabia Naimat; Iram Naeem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
In order to address the growing concern about mental health concerns among university students in Pakistan, this article focuses on the causes of these difficulties and suggests viable remedies. The research review highlights the effects of peer pressure, technology use, family expectations, financial restrictions, social and cultural norms, academic pressure, and financial restraints on students’ mental health. Low mental health literacy and job market uncertainty make the problem worse. The study’s aims include determining the incidence of mental health problems among university students in Pakistan, identifying risk factors, and examining the links between academic pressure, job insecurity, and mental health outcomes. The study uses a cross-sectional design and a quantitative research methodology to collect data from 460 Pakistani university students using stratified random sampling. The examination of the data suggests that students experience moderate degrees of anxiety, despair, stress, loneliness, and sleep disruptions. Technology usage, financial stress, and academic stress are all quite common, but social support could be a buffer against mental health problems. Influences from culture barely make a difference.The study suggests campaigns to lessen stigma and raise awareness of mental health issues, stress management programmes, financial aid efforts, guidelines for safe technology use, and the encouragement of social support networks among students. Pakistani universities may greatly improve their students’ overall wellbeing and academic achievement by giving mental health education and assistance a high priority.